A new hybrid heatsink design for enhancement of PV cells performance. (November 2022) - Torbatinezhad, A.; Ranjbar, A.A.; Rahimi, M.; Gorzin, M.
Abstract: For enhancing the proficiency of photovoltaic cells used in the parabolic concentrated photovoltaic system, a type of wavy mini-channel heatsink, coupled with jet impingement is used in the present study. In this regard, the impacts of wavelengths of mini-channel and jet angles have been investigated to achieve a higher performance. Moreover, so as to assess the effects of water flow rate variations as a coolant, the cooling performance is examined for 5 values of coolant flow rates. The outcome of the investigation is divided into two important aspects: first, the effects of wavelengths on the average cell surface temperatures; electrical and thermal efficiencies; exergies; and heat transfer coefficient is examined and second, the impacts of different jet angles on the mentioned parameters are explored. Studying the solar cell's temperature, it is revealed that the average temperature reduces up to 4.46% as the wavelength of the mini-channel diminishes from 12.5 mm to 5 mm for m ̇ = 0 . 08 kg/s which results in performance improvement up to 28.77%. In addition, the temperature reduces about 12 centigrade when the coolant rate ascends from m ̇ = 0 . 05 kg/s to m ̇ = 0 . 15 kg/s for the impingement angle of 30 degrees. As a result, this mass flow rate increment offers up to 29.65% electrical efficiency.